Relationship Between c-Jun N-terminal Kinase and Depression - Ma Hongpeng (E3S Web of Conferences, 2020)
Depression is one of the most common emotional disorders. The cause of depression is still not clear. C-Jun N-terminal kinase (JNK) is one number of mitogen activated protein kinase (MAPK) family, which is closely related to the occurrence of many diseases. At present, it is believed that JNK plays an important role in the parthenogenesis of depression, but the specific mechanism is not clear. This review will focus on the possible mechanism of JNK protein and JNK signaling pathway affecting the parthenogenesis of depression.